DYNAMIC ASSESSMENT OF THE FUNCTIONS OF MUCOCILIARY CLEARANCE IN PATIENTS WITH AN INTUBATION TUBE AND NASGASTRAL PROBE - Safoev Mukhammadorif Rakhimjon ugli; Ashurov Azimzhan Mirzazhanovich; Abdullaev Khabibulla Nasratullaevich (International Journal on Orange Technologies, 2021)
The functional state of the nasal mucosa in patients was assessed by the time of MTS using visual (methylene blue) indicators according to the method of S.Z. Piskunov et al. 75 patients with various pathologies and brain injuries in serious condition were examined. The patients were divided into groups: 1st group is patients with severe TBI; 2nd patients with TBI and nasogastric tube (NGZ); 3rd patients with severe TBI and nasotracheal intubation (NTI); and the 4th group with TBI and orotracheal intubation (OTI) and the control group, these are patients in the intensive care unit without TBI. We found that when NTI and NGZ are in the nasal cavity for more than 4-5 days, there is a risk of nosocomal sinusitis. This alarms us to take preventive measures to prevent nosocomial sinusitis from the first day after hospitalization of the patient